Pengaruh Tax Planning, Mekanisme Bonus dan Kepemilikan Asing terhadap Transfer Pricing Perusahaan Makanan dan Minuman Periode 2019-2021 - Andry Sugeng; Agus Afandi; Khusnul Khuluqi (INOVASI, 2023)
The study aims to analyze and obtain empirical evidence of the influence of tax planning, bonus mechanisms and foreign ownership of transfer pricing in the sub-sector food and beverage manufacturing companies in the BEI period 2019-2021. Independent variables in the study are tax planning, bonus mechanisms and foreign ownership. While the dependent variable in this study is transfer pricing. This research analysis method uses multiple regression analysis. The sample collection was done using purposive sampling method so that the sample amount was obtained as many as 14 companies with a span of 3 years, then obtained 55 company financial statements data as research observation. The results of this study showed that (1) tax planning has no effect on transfer pricing, (2) bonus mechanisms have no effect on transfer pricing, (3) foreign ownership has a significant effect on the company’s value, (4) tax planning, bonus mechanisms and foreign ownership simultaneously affects transfer pricing.